∆133p53 isoform promotes tumour invasion and metastasis via interleukin-6 activation of JAK-STAT and RhoA-ROCK signalling - Hamish Campbell (Nature Portfolio, 2018)
Aberrant expression of the Δ133p53 isoform is linked to many cancers. Here, the authors utilise a model of the Δ133p53 isoform that is prone to tumours and inflammation, showing that Δ133p53 promotes tumour cell invasion by activation of the JAK-STAT and RhoA-ROCK pathways in an IL-6 dependent manner.